2008
DOI: 10.1017/s0033291707002474
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among persons with arthritis: results from the World Mental Health Surveys

Abstract: Background-Prior studies in the USA have reported higher rates of mental disorders among persons with arthritis but no cross-national studies have been conducted. In this study the prevalence of specific mental disorders among persons with arthritis was estimated and their association with arthritis across diverse countries assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 37 publications
8
64
1
5
Order By: Relevance
“…Bei muskuloskelettalen Erkrankungen -insbesondere bei Arthropathien und Rückenschmerzen -ist bekannt, dass eine enge Beziehung zwischen der somatischen Erkrankung und psychischen, insbesondere depressiven Beschwerden und Störungen, besteht [4,5,6,7,8,9,10]. Aufgrund des hohen, stetig steigenden Anteils von Patienten mit muskuloskelettalen Erkrankungen und der resultierenden negativen gesundheitsökonomischen Folgen [11,12] sind ein frühzeitiges Erkennen, eine valide Diagnose und eine adäquate Behandlung komorbider psychischer Störungen notwendig.…”
Section: Leitthema: Psychische Komorbidität Bei Chronischen Erkrankungenunclassified
“…Bei muskuloskelettalen Erkrankungen -insbesondere bei Arthropathien und Rückenschmerzen -ist bekannt, dass eine enge Beziehung zwischen der somatischen Erkrankung und psychischen, insbesondere depressiven Beschwerden und Störungen, besteht [4,5,6,7,8,9,10]. Aufgrund des hohen, stetig steigenden Anteils von Patienten mit muskuloskelettalen Erkrankungen und der resultierenden negativen gesundheitsökonomischen Folgen [11,12] sind ein frühzeitiges Erkennen, eine valide Diagnose und eine adäquate Behandlung komorbider psychischer Störungen notwendig.…”
Section: Leitthema: Psychische Komorbidität Bei Chronischen Erkrankungenunclassified
“…Similarly, adults who were exposed to parental substance abuse in childhood experience higher rates of depression in adulthood [18]. Data collected from cross-sectional population-based research indicates that there is a positive correlation between depression and self-reported arthritis conditions [22] and prospective research confirms these findings [35].…”
Section: International Journal Of Population Researchmentioning
confidence: 97%
“…For example, parental addiction has been associated with adult children's alcohol abuse [17,18], smoking [17,19], and other substances abuse [7,17,18]. In turn, these health behaviors, particularly cigarette smoking [20,21] and alcohol consumption [22], are associated with an elevated risk of adult onset arthritis [8].…”
Section: International Journal Of Population Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…35,37,315 Although many of the factors associated with the future course of OA are not modifiable at the point of care (e.g. age, sex, symptom duration, severity of underlying structural changes to the joint [316][317][318][319] ) comorbid depression and anxiety are an exception as they are potentially treatable.…”
Section: The Hypothesis Under Testmentioning
confidence: 99%